King's sister--queen of dissent : Marguerite of Navarre (1492-1549) and her evangelical network - Reid, Jonathan A. (Studies in medieval and Reformation traditions, 2009)
"This study reconstructs for the first time Marguerite of Navarre's leadership of a broad circle of nobles, prelates, humanist authors, and commoners, who sought to advance the reform of the French church along evangelical (Protestant) lines. Hitherto misunderstood in scholarship, they are revealed to have pursued, despite persecution, a consistent reform program from the Meaux experiment to the end of Francis I's reign through a variety of means: fostering local church reform, publishing a large corpus of religious literature, high-profile public preaching, and attempting to shape the direction of royal policy. Their distinctive doctrines, relations with major reformers - including their erstwhile colleague Calvin - involvement in major Reformation events, and the impact of their unsuccessful attempt are all explored."--Publisher's website